Strategi marketing syariah dalam menghadapi persaingan bisnis - Najiya, Usluki (Maliki Interdisciplinary Journal, 2023)
The rapid development of business has encouraged many entrepreneurs to start businesses and expand their networks. However, trade secrets are very vulnerable to disclosure or theft of food and beverage recipes. The purpose of this research is to examine the regulations and legal sanctions for violations of trade secrets in the food and beverage industry franchise business. This notation is a type of normative legal research with a legal approach. The results of the study show that trade secrets in the food and beverage industry are protected in such a way that recipes cannot be published without a licensing agreement. Administrative sanctions and criminal sanctions can be applied to legal sanctions against parties who disclose trade secrets as regulated in the Trade Secret Law No. 30 of 2000 and the Civil Code and the Criminal Code. When trade secrets are violated, it can be resolved through legal or extrajudicial means, or through consent agreements.